Persistent Atraumatic Knee Pain in a Teenage Female with Bony Protuberance Secondary to Hook-Shaped Osteochrondroma - Adityanarayan Rao; Joshua Pryor; Jaclyn Otero; Molly Posa (Hindawi Limited, 2021)
A 13-year-old female presented at her pediatrician's office with a complaint of sharp, intermittent, right-sided knee pain that had been present for the previous three days without any known trauma and no association with activity. Her medical history was significant for fractures, and on physical exam, there was a hard mass palpated on the medial aspect of her distal thigh that was nontender, nonmobile, and without overlying skin changes. The plain radiograph findings were consistent with a hook-shaped osteochondroma of the right medial distal metaphysis. Orthopedics recommended conservative management with continued ibuprofen for pain and six-week follow-up with repeat radiograph to evaluate for progression. The follow-up radiograph showed no interval growth. However, due to continued pain, the patient had surgical excision of the osteochondroma six months after initial presentation, allowing her to finish her current soccer season. The surgery was successful, and the patient did well after operation with no residual pain.